DINAMIKA PENGAKUAN DAN PERLINDUNGAN HUKUM ADAT DALAM PERSPEKTIF GENERASI MUDA: TINJAUAN KEPUSTAKAAN TERHADAP REGULASI TURUNAN DAN TANTANGAN IMPLEMENTASI DI INDONESIA - Gunawan Widjaja; Wagiman (INTELIGENSIA MEDIA, 2025)
The recognition and protection of customary law in Indonesia is an issue that continues to evolve amid regulatory dynamics and implementation challenges. This study aims to analyse the dynamics of recognition and protection of customary law from the perspective of the younger generation through a literature review of derivative regulations and practical challenges in the field. The research method used is a literature review, examining legislation, official documents, and previous research findings related to customary law. The review findings indicate that although derivative regulations such as national laws, government regulations, and local regulations have provided a formal framework for the recognition of customary law, implementation in the field often faces obstacles in the form of complex bureaucracy, regulatory disharmony, and pressure from modernisation and commercialisation. The role of the younger generation is significant in addressing these challenges through active involvement in advocacy, education, and digital innovation. Their involvement not only preserves the sustainability of customary law but also encourages regulatory reforms that are more responsive to the future needs of indigenous communities. This study recommends synergy between policymakers, legal structures, and the empowerment of the younger generation to strengthen inclusive and equitable protection of customary law.